ANALYSIS OF SIGNALIZED INTERSECTION PERFORMANCE: A CASE SIMPANG EMPAT SMPN 1 MAJALENGKA - Sayid Muhammad Akbar; Ade Jaya Saputra (Fakultas Teknik Sipil dan Perencanaan, 2024)
Economic and health aspects are most significantly affected by traffic congestion due to delays in the execution of daily tasks, causing a huge waste of time, effort, and focus, as well as other additional costs. Like the intersection at SMPN 1 Majalengka or what is usually called the Abok intersection, which is one of the access roads to the economic center, the traffic problem that often occurs at the intersection at SMPN 1 Majalengka is congestion, especially at rush hour. traffic flow is increasing. denser than at other times. The aims of this research is to analyze the traffic engineering that occurs at the signalized intersection of SMPN 1 Majalengka which can cause congestion so that in the future this research will look for solutions to be more careful in traffic engineering. The research methodology used in this research is a qualitative method. This research was conducted at the Abok signalized intersection which is located near SMPN 1 Majalengka, Majalengka Regency. Based on the table above, it can be seen that the degree of saturation in the four directions has a value of 0.88. It can be concluded that the degree of saturation in all four directions is the same, namely 0.88 and according to MKJI 1997 this figure is included in the creeping dense category. The resulting degree of saturation is quite high, causing the service level value to creep up. This result will increase the risk of traffic jams at the intersection. So attention is needed in carrying out good traffic management.